Tradisi Her Tutu (Kawin Paksa) dalam Tatanan Hukum Adat Suku Kemak Kampung Sadi Kabupaten Belu Ditinjau dari Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Maritha Almeida Soares Fahik; Karolus Kopong Medan; Daud Dima Tallo (Universitas Sains dan Teknologi Komputer, 2024)
Legal protection for the tradition of forced marriage has been regulated in the form of Law Number 12 of 2022 concerning criminal acts of sexual violence. With the enactment of Law Number 12 of 2022, it guarantees legal certainty for victims of forced marriage in protecting their rights. The purpose of this research is to determine the essence of the